Biochemical and genetic analyses of a catalase from the anaerobic bacterium Bacteroides fragilis. - Rocha, Edson R.; Smith, C. Jeffrey (East Carolina University, 1995)
A single catalase enzyme was produced by the anaerobic bacterium Bacteroides fragilis when cultures at late log phase were shifted to aerobic conditions. In anaerobic conditions, catalase activity was detected in stationary-phase cultures, indicating that not only oxygen exposure but also starvation may affect the production of this antioxidant enzyme. The purified enzyme showed a peroxidatic activity when pyrogallol was used as an electron donor. It is a hemoprotein containing one heme molecule per holomer and has an estimated molecular weight of 124,000 to 130,000. The catalase gene was cloned by screening a B. fragilis library for complementation of catalase activity in an Escherichia coli catalase mutant (katE katG) strain. The cloned gene, designated katB, encoded a catalase enzyme with electrophoretic mobility identical to that of the purified protein from the B. fragilis parental strain. The nucleotide sequence of katB revealed a 1,461-bp open reading frame for a protein with 486 amino acids and a predicted molecular weight of 55,905. This result was very close to the 60,000 Da determined by denaturing sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the purified catalase and indicates that the native enzyme is composed of two identical subunits. The N-terminal amino acid sequence of the purified catalase obtained by Edman degradation confirmed that it is a product of katB. The amino acid sequence of KatB showed high similarity to Haemophilus influenzae HktE (71.6% identity, 66% nucleotide identity), as well as to gram-positive bacterial and mammalian catalases. No similarities to bacterial catalase-peroxidase-type enzymes were found. The active-site residues, proximal and distal hemebinding ligands, and NADPH-binding residues of the bovine liver catalase-type enzyme were highly conserved in B. fragilis KatB. Originally published Journal of Bacteriology, Vol. 117, No. 11, June 1995
Keywords: Anaerobic bacteria; Catalase enzyme; Antioxidant enzyme